Investigation of hemp (Cannabis sativa L.) crop weediness (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The investigation of hemp crop weediness was carried out at the Upytė Experimental Station of the Lithuanian Research Centre for Agriculture and Forestry in 2014. Bi-factorial trial was carried out: Factor A – variety (A1 – USO 31; A2 – Bialobrzeskie); Factor B – sowing rate (B1 – 45 kg ha-1; B2 – 70 kg ha-1). Data showed that seed rate had a significant influence on crop density at full hemp emergence as well as at harvesting time. Rainy vegetation period was favourable not only for hemp growing, but for weeds as well. Crop density (resulted by seed rate) had a significant influence on crop weediness – significantly more weeds (in average 166 plants m-2) were found in the plots with seed rate of 45 kg ha-1, consequently at lower crop density, and under 140 weed plants m-2 were found in the plots with seed rate of 70 kg ha-1, consequently at higher crop density. Hemp crop weediness at harvesting time was much lower than that at the beginning of vegetation; reduction of weediness over the vegetation period was close to 87-90 percent.